Island of the Blue Dolphins./ Scott O'Dell - O'Dell, Scott, 1898-1989. (New York : Houghton Mifflin, 1960)
The gripping story of young Karana, an Indian girl who survives by herself for eighteen years on a deserted island off the California coast. A quiet acceptance of fate characterizes her ordeal.
G9
Keywords: Fiction; Survival -- Fiction